Volunteering and activism as forms of active citizenship (a case study) - Pecníková, Jana (Teorija in praksa, 2016)
The article deals with volunteering as a form of active citizenship related to the concept of participatory and democratic citizenship. The theoretical part of the study concerns the different approaches to the dimensions of citizenship (especially cultural and social), while the article's second part is constructed as a case study of volunteer forms of active citizenship in the urban environment of the city of Banska Bystrica (Slovakia) that was realised through a series of semi-structured, in-depth qualitative interviews. The conclusion shows the trends and limitations in the application of volunteering to local society.
Keywords: Citizenship; Državljanstvo; Prostovoljno delo; Slovakia; Slovaška; Volunteer work